Autogenous Dental Transplantation in a Patient Undergoing Class III Dento-Facial Deformity - Quirino, Lilian Caldas [UNESP]; Carvalho, Pedro Henrique de Azambuja; Rocha, Audrey Foster Lefort; Gabrieli, Marisa Aparecida Cabrini; Pereira-Filho, Valfrido Antonio (Wolters Kluwer, 2020)
Dental transplantation is an alternative for rehabilitation with a high success rate. This article presents a clinical case of autogenous dental transplantation in a 17-year-old male patient undergoing treatment for Class III dento-facial deformity. After 32 months followup, low-cost rehabilitation was possible, and without prejudice to ortho-surgical treatment.